Educational card game for chinese character learning / Ting Hie Ling and Lam Kai Chee - Ting, Hie Ling; Lam, Kai Chee (Universiti Teknologi MARA, Kedah, 2021)
Chinese character s often categorized as logographic writing systems . In an ideographic or comparison, Chinese characters have different writing systems with alphabetical writing systems. Learners show unsatisfactory results due to the complexity of orthographic structure in Chinese characters which also led to a negative impact on Mandarin learning. Thus, an educational card game, namely "Chinese Character Battle (CCB)" was designed for Mandarin learners to learn Chinese characters. This educational card game was implemented in Mandarin as Foreign Language (MFL) classroom for this preliminary study as a step to explore users' perceptions about CCB and the impact of CCB in Chinese character recognition. An online survey, pre-test, and post-test were used to achieve the objectives of this study. A recorded video of "How to Play CCB" was shared with participants prior to the use of CCB. Non-native Chinese learners from University Teknologi Mara, Sarawak branch, Mukah campus participate in this study. The findings of this study revealed that: (1) participants responded positively towards the use of CCB; (2) the implementation of CCB showed positive impact on Chinese character recognition. Hence, it could be concluded that CCB is an effective and useful supplementary learning tool for Mandarin learners to improve their Chinese character recognition